Impact of endometrioma management strategies on ovarian reserve over the follow-up period, a prospective longitudinal study - Aslan, Kiper; Kasapoglu, Isil; Kosan, Bahadir; Gurbuz, Tansu Bahar; Muzii, Ludovico; Uncu, Gurkan (Frontiers in Endocrinology, 2025)
BackgroundThe effects of current treatment options for endometrioma on ovarian reserve remain controversial. Recent advancements in surgical techniques may challenge the previously established evidence regarding the detrimental effects of surgery on ovarian reserve. Additionally, whether medical suppression therapy provides a protective effect during this process remains an unanswered question. Furthermore, the impact on ovarian reserve in patients managed expectantly, without active intervention, is unclear.ObjectiveThis study aims to evaluate the effects of endometrioma per se or its treatment modalities on ovarian reserve.MethodsIn this prospective study, eighty women diagnosed with endometrioma via ultrasonography and twenty age-matched healthy women as controls were enrolled. The study group was divided into four subgroups, each consisting of twenty patients, based on the treatment modality received: expectant management, oral contraceptive pills (OCP), dienogest, and surgery. All participants underwent baseline ultrasonographic evaluations and blood sampling to determine serum anti-Müllerian hormone (AMH) levels at the time of enrollment. Follow-up assessments, including repeat ultrasonography and AMH measurements, were conducted six months after the initial evaluation.ResultsThe median six-month decline in serum AMH levels was 19% in the expectant management group, 26% in the OCP group, 21% in the dienogest group, 38% in the surgery group, and 8% in the healthy controls. Thus, statistically significant differences in AMH decline were observed between the OCP group and healthy controls (p = 0.034), and between the surgery group and healthy controls (p = 0.001).ConclusionDespite advances in surgical techniques and precautions, surgical excision of endometriomas continues to pose a risk to ovarian reserve. Treatment with both dienogest and OCP is associated with a decrease in serum AMH levels, although the decline appears less significant with dienogest. Patients managed expectantly also showed a progressive decline in ovarian reserve compared to healthy controls.Trial Registration NumberClinical Trials, NCT03620838.